Enhancement of antibacterial activity through phyto‐fabrication of silver nanoparticles with Ficus thonningii aqueous extracts - Dickens A. Ondigo; Were L. L. Munyendo; Dickson Andala; Apollo O. Maima; Josephat M. Mosweta; Kevin W. Odhiambo (IET Nanobiotechnology)
Abstract The World Health Organisation reports higher levels of bacterial resistance to cephalosporins and carbapenems of above 54%. The sufficient redox capabilities of Ficus thonningii phytochemicals for Ag+ reduction to Ag0 and ultimately aggregation to nucleation are exploited for the first time in attempting to enhance the antibacterial activity. Solution colour change to brown due to surface plasmon resonance phenomenon confirmed nanoparticle fabrication with a UV/Vis absorption peak at 426 nm. Fourier Transform Infrared spectra revealed functional groups (C=C at 1620–1680 cm−1; C=H at 1400–1600 cm−1 aromatics) for encapsulation, stabilisation, and reduction of the silver ion. The Dynamic Light Scattering technique verified F. thonningii encapsulated silver nanoparticles particle size of 57.84 nm with a negative zeta potential (−19.8 mV) as proof of stability. The surface, shape and topographical features were shown by Scanning Electron Microscopy as spherical orientations. An enhanced antimicrobial efficacy was displayed by the nanoparticles (inhibition zones of 26.1, 24.1 and 15.2 mm from 11.5, 10.6 and 6.5 mm) for Staphylococcus aureus, Streptococcus pyrogenes and Escherichia coli, respectively, compared to Flucloxacillin standard that was in the ranges of 21.5, 23.5 and 25.7 mm. The enhanced potency provides a basis for diversified approaches of generating novel drugs for treating bacterial infections.